Examining the liquidity risk in the household sector and the policy implications - Young Il Kim (Korea Development Institute (KDI), 2020)
In the wake of an unprecedented health crisis, households who lack liquid assets that could tackle their growing deficit (=income-expenditure) will endure severe financial difficulties. The share of households facing liquidity risk will increase as incomes fall by bigger margins and exposure to the shock intensifies. The liquidity risk resulting from COVID-19 will be even more pronounced among the economically vulnerable; specifically, those in the bottom quintile in terms of income and net assets, and temporary and daily wage workers. Households at liquidity risk are particularly concentrated in the low income quintile. As such, a short-term income support program offering even a small amount of aid (e.g. 1 million won) could greatly help to reduce their liquidity risk. In terms of support for at-liquidity-risk households, a selective approach which focuses the income support on the economically vulnerable and provides credit support in the form of collateral loans to asset-owning households will be more effective in easing the liquidity risk and the government's fiscal burden.
Keywords: 330